Healthcare engineering : proceedings of CAETS 2015 Convocation on Pathways to Sustainability - Shorey, Rajeev; Ghosh, P., 1947- (Springer, 2017)
The book contains the proceedings of CAETS 2015 Convocation on 'Pathways to Sustainability: Energy, Mobility and Healthcare Engineering' that was held on October 13-14, 2015 in New Delhi. This 3 volume proceedings provide an international forum for discussion and communication of engineering and technological issues of common concern. This volume talks about 'Healthcare' and includes 11 chapters on diverse topics like regenerative engineering, big data analytics in healthcare, molecular science, rising expenditure on health issues, adoption of personalized medicine, etc. The contents of this volume will be useful to researchers and healthcare professionals.
Includes author index.
Keywords: Biomedical engineering -- Congresses.; elektronické knihy; electronic books